(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
Tolerance and flexibility in adopting talfiq in controversial fatwa cases is a very relevant and complicated topic in the study of Islamic jurisprudence. This article aims to examine the concept of talfiq and how it is applied in formulating fatwas that create polemics. talfiq is an approach used to combine views from various schools of Islamic jurisprudence in formulating fatwas. This approach considers a balance between flexibility in dealing with complex practical problems and the diverse needs of Muslims. However, the practice of talfiq also gives rise to debate among ulama. Some see talfiq as a form of tolerance and inclusiveness in response to changing times, while others still adhere to the conservative principles of their respective schools of thought. In the case of fatwas which are a source of debate, merging madzhab through talfiq could be a solution that is more inclusive and relevant to current developments. Decisions regarding controversial fatwas, which involve the use of talfiq, must be based on in-depth study, ongoing dialogue between ulama from various schools of thought, as well as considerations of Islamic values, the benefit of the people, and the principles of justice. An attitude of mutual respect and inclusion in discussions is very important to achieve a broader and more measurable understanding.